Pengaruh Media Social Marketing Terhadap Customer Loyalty Dan Buying Decision Sebagai Variabel Intervening Terhadap Pengguna Xl-Axiata - Pratama, Yehezkiel Pria; Prasetya, Adhitya Yoga (Politeknik Negeri Ambon, 2024)
The year 2024 is known as the post gen z era, this era is a new era where everyone is already using gadgets. If you want to connect to the internet, you have to buy a starter pack. This research is a study with the aim of analyzing the impact of social media marketing on customer loyalty and buying decisions as an intervening variable. The sample was selected by purposive sampling with 100 respondents who used XL-Axiata starter pack cards. by distributing questionnaires online via google forms. Data analysis was performed using the PLS-SEM (Partial Least Squares-Structural Equation Modeling) method using SemPLS software. The results showed that 1) Media Social Marketing has an effect on Customer Loyalty, 2) Media Social Marketing affects Buying Decision, 3) Buying Decision affects Customer Loyalty, 4) Buying Decision affects Customer Loyalty